Identification of Genetic Risk Factors Associated With Herbal and Dietary Supplement–Induced Acute Liver Failure Using Whole Exome Sequencing Analysis - Tsung-Jen Liao; Menghang Xia; Dingyin Tao; Yanyan Qu; Baitang Ning; Jody A. Rule; William M. Lee; Ruili Huang; Jorge Rakela; Minjun Chen (Gastro Hep Advances)
Background and Aims: Herbal and dietary supplements (HDS) have been associated with liver injury and severe liver disease, including acute liver failure (ALF), collectively referred to as HDS-induced ALF (HDS-ALF). With the global increase in HDS usage, reports of HDS-ALF cases have also risen. Methods: Genetic analysis was conducted using whole exome sequencing data from 23 HDS-ALF cases, with population controls sourced from the 1000 Genomes Project. Single-nucleotide polymorphisms (SNPs) with chi-square test P values less than 5 × 10−8 and stable allele frequencies across different ethnicities and healthy controls were considered statistically significant. Variants were also analyzed based on supplement type (herbal vs dietary) and sex (female vs male). Results: Thirty-three SNPs were statistically significant (P < 5 × 10−8), predominantly located in human leukocyte antigen (HLA) genes (HLA-A, HLA-B, HLA-DQA1, and HLA-DRB1) and estrogen-related receptor alpha (ESRRA). The top SNPs, including rs17879990 (HLA-A), rs1131500 (HLA-B), and rs1161801407 (HLA-DRB1), showed strong associations. In subgroup analyses, 4 SNPs were significant in the herbal product group and 3 in the dietary supplement group. Gender-based analyses revealed 15 significant SNPs in females and 8 in males, particularly 7 SNPs within HLA-B and HLA-DQA1, appeared female-specific. Conclusion: This study identifies specific HLA and ESRRA gene variants as genetic risk factors for HDS-ALF, with significant associations observed across HDS exposures. The findings suggest potential cross-gender risks, particularly for certain HLA and ESRRA SNPs, while highlighting female-specific vulnerabilities within HLA-B and HLA-DQA1 variants.